The Scribe of Sufi-Philosophical Letters: Shaykh Yūsuf of Makassar’s Formative Decades (1640s-1660s) in Arabia and Syria - Umam, Zacky Khairul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This article addresses the circumstances surrounding Shaykh Yūsuf’s pursuit of knowledge, which involved traveling overseas via India to study and teach in Ottoman Arabia and Syria. The article’s main objective is to focus on the period during which Shaykh Yūsuf played an intellectual role as a scribe in Aleppo, Damascus, and Medina between the 1650s and the 1660s. This will be achieved by utilizing the manuscript collections at the Staatsbibliothek zu Berlin, the Firestone Library of Princeton University, and the National Library of Indonesia, in addition to other archival evidence. These underexplored manuscripts will provide a more comprehensive account of Shaykh Yūsuf’s Arabian years, which I contend were a pivotal period in his intellectual development. Moreover, this period offers an additional perspective on the dissemination of knowledge from the post-Timurid intellectual tradition, which was oriented towards the advancement of theological-philosophical sciences, and which became prevalent in Medina before being disseminated in the second half of the seventeenth century.